2018
DOI: 10.1021/acs.jpcc.8b02798
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Adsorption on Rh(111): A New Perspective on Intermolecular Interactions and Molecular Ordering

Abstract: The adsorption of benzene on the Rh(111) substrate was investigated through scanning tunneling microscopy (STM) imaging and density functional theory (DFT) calculations. Experiments were carried out at various surface coverages, with the amount of benzene adsorbed determined to influence the molecular adsorption site, the intermolecular interactions, and the interaction between the molecule and the substrate. At a sub-monolayer coverage of the surface, the molecules are disordered and kept apart by a strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 78 publications
(224 reference statements)
1
4
0
Order By: Relevance
“…The only exception is Cu(111) where the physiosorbed BZ is unaffected resulting in identical brightness for six equivalent phenyl C atoms. For validity, we note here that the features of our simulated STM images show excellent match with those of low-coverage adsorbed BZ observed in previous experiments/simulations . For comparison, the brighter spot can be identified as the O atom of adsorbed phenol on metal surfaces, suggesting that the negatively charged O atom with the intrinsically rich electron density around O nucleus is competitive with those of binding C atoms of the phenyl ring, regardless of the metals (Figure S6).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The only exception is Cu(111) where the physiosorbed BZ is unaffected resulting in identical brightness for six equivalent phenyl C atoms. For validity, we note here that the features of our simulated STM images show excellent match with those of low-coverage adsorbed BZ observed in previous experiments/simulations . For comparison, the brighter spot can be identified as the O atom of adsorbed phenol on metal surfaces, suggesting that the negatively charged O atom with the intrinsically rich electron density around O nucleus is competitive with those of binding C atoms of the phenyl ring, regardless of the metals (Figure S6).…”
Section: Resultssupporting
confidence: 83%
“…STM , is a highly sensitive technique for probing both electronic and geometric structures of a surface, providing information on atom-resolved structures of the surface (or interface) and adsorbate geometry. , For π-conjugated aromatic molecules adsorbed on metal surfaces, numerous STM studies have been reported over the years including BZ adsorbed on Rh(111), , Pt(111), Ni(110) and Cu(110), , and Si(100) . Our DFT-simulated STM images of BZ adsorbed on eight close-packed metal surfaces studied are displayed in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies, the bridge 30°site was found to be the most favourable. However, the most stable adsorption site for aromatic rings on metallic surfaces is still under debate as demonstrated by the recent work of Treanor et al [34] who found the hollow hcp site to be (slightly) favourable on Rh(111). Lower row: The labelling schemes we use in this study.…”
Section: In Search Of Stable Keto and Enol Conformers On The Pd(111) mentioning
confidence: 99%